(3JGL GdeUGOQs - (3CMeO Hf Ydj Hf eMeO GdHjgbj, hjbGd dg CHh LYaQc,J (B544 (3g` s ((3eMeO Hf eSYhO s)
(3ChdgG (B:s
(3GdebOeI ajgG YTQI aUhd (B: (3GdaUd GdChd ai MbjbI GdaYd hGdeUOQ CeG GdaYd agh GddaX GdOGd Ydi eYfi ai faSg ebJQf HReGf eMUd , aGddaX GdOGd Ydi eYfi LfS jTed GdGSe hGdaYd hGdMQa s
(3BNQgG (B:s
(3HGH GdCaYFdGd (B: (3H(B: (3EJdCH GdCeQ ESJbGe CTQCH dg eO YfbI djfXQg hGdUMjM Cf GdWeCfjfI GSe Cbje ebGe GdeUOQ hGddjd (B: (3CXde LOkG GcHCf JbHV Je GdcJGH s
(3fSNI KGfjIs
(3fbdgG GdfGSN ef CUd GdeDda HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs